Pengaruh Kinerja Perusahaan Terhadap Praktik Manajemen Laba pada Emiten Indeks Saham Syariah Indonesia - P. Prasojo; Islahuda Rahma Fatayati (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
The research focuses on practice of earnings management. Earnings management is an action performed by managers by giving a good signal to investors through financial statements. The purpose of this research is to test and analyze the influence of Net Profit Margin, Size, Age and Leverage on earnings management practices at companies listed in Indonesia Sharia Shares Index (ISSI) for 2012-2016 period. Based on 127 observed firms, panel data regression of fixed effect models has been used to investigate the relevance of earnings management practices. The results shows that simultaneously Net Profit Margin, Company Size, Age Company (Leverage) and Leverage influence earnings management practice. Partially, the variable Net Profit Margin and Company Size has no significant effect on earnings management practices. Meanwhile, Age of Company and Leverage have significant effect on earnings management practices.